Characteristics and Distribution of the Productive and Reproductive Roles of Female Lurah in Bekasi Regency - Harahap, Hamida Syari; Vitayala S Hubeis, Aida; Saleh, Amiruddin; Matindas, Krishnarini (Jurnal Penyuluhan, 2020)
The objectives of this article are to analyze some characteristics such as education, ethnicity, duration of duty, as well as internal and external environmental supports, situated knowledge, role distribution, and leadership of Female Lurahs in Bekasi Regency. The research applied a critical paradigm with a qualitative approach. NVivo 12 software is used for data analysis. The informants are three Female Lurahs, who have excellent achievements and 18 additional informants who actively took part in kelurahan activities, those were respectively three Chief RTs, RWs, community leaders, and the other nine health cadres. The location of the study was determined purposefully. The research results showed that the three Female Lurahs had different perspectives in carrying out leadership roles. Characteristic differences were in the forms of exemplary, paying attention to manners, and selves-reliance. The situated knowledge differences were initiatives, openness in communication, and coordination in carrying out tasks. The different point of vies in the roles of division was that the kelurahan residents were considered as their children and their partners. The uniqueness of the research was that the standpoint theory was applied to analyze the role of the Female Lurahs as Leaders at the grass-root levels. The importance of different points of view in carrying out leadership roles in the research was that the leadership was carried out regarding the situation, conditions, and characteristics of residents.